PROFILE PEMBERITAAN PEMBANGUNAN PERIKANAN DAN KELAUTAN PADA SURAT KABAR KALTIM POST PERIODE 1JULI-31DESEMBER 2020: Fisheries and Marine Development Reporting Profile in the Kaltim Post Newspaper Period 1 July – 31 December 2020 - dwi larasati; Erwiantono; Juliani (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
This study aims to determine the frequency of news on fisheries development published in the Kaltim Post Newspaper from 1 July to 31 December 2020 based on Regional Origin, Main Topics, News Layout Patterns, News Volume, Reviewing Opinions of Experts and Academics, Expert Practitioners' Opinions. Or Journalism Expert Print Media. The sampling method used is the Census Method and purposive sampling by taking a sample of News in the Period 1 July – 31 December 2020, interviewing 3 Fisheries Experts, 1 Bureaucrat of the Fisheries and Marine Service of East Kalimantan Province, and 1 Journalist. The data analysis method used is News Frequency and Expert Opinion. The results of this study indicate that the appearance of news is 266. Dominated in December 58 News, Frequency of Originated from Balikpapan 64 News (24.06%), 255 news group (95.90%), Non-Headlines Layout 199 News, Topics of News Conservation of Nature Protection and Ecotourism 63 (23.68%), Loaded Fishery News Volume (84,338cm), News Volume Based on December Area 19,288cm (22.87%), Balikpapan Dominated Area Volume 19,406cm (23.01%), Non-Headline Layout Volume 63.204cm (74,94%), Type of Article Nomination Area News 79,102cm (93.72%), Volume of Main Topic News Conservation of Nature Protection 22,133cm (26.24%) Based on the Expert Opinion of Fisheries Academics and Bureaucracy, the news profile uses easy-to-understand language, the written material has a scientific concept, does not deviate, the data presented is not relevant, the news sources are clearly listed, the news is dominated by mixing facts and opinions, preferably the content contained in news is for optimizing employment absorption, and the provision of animal protein sources for public consumption, coastal community income, based on expert opinions. and using regional languages, media experts also argue that the news presentation in the number of columns is sufficient. The size of the letters presented is already standard news. Keywords : Development News, News Frequency, News Volume, Expert Opinions of Bureaucrats, and Journalis